DISORDER OF SEX DEVELOPMENT : AMBIGUOUS GENITALIA, PARTIAL ANDROGEN INSENSITIVITY SYNDROME - Rajuddin, Rajuddin; Fauzan, Fauzan (Fakultas Kedokteran Universitas Malikussaleh, 2017)
Disorders of sex development (DSDs) also known as ?intersex? are congenital condition by mismatch in which chromosomal, gonadal and anatomical. One in 4.500 infants is born with abnormalities of External genitalia, and mostly unexplained in molecular term. Androgen Insensitivity Syndrome (AIS) is a common cause of DSDs. Partial Androgen Insensitivity Syndrome (PAIS) is one of three broad subdivided phenotypes of AIS. Typically, characterized by evidence of feminization (i.e., undermasculinization) of the external genitalia at birth, abnormal secondary sexual development in puberty, and infertility in individuals with a 46,XY karyotype. In males characterized, Pais is common to observe a micropenis, hypospadias, and cryptorchidism. Individuals with PAIS that are characterized as women have been observe to have clitoromegaly and a fused labia during puberity . We reported a 13 year old child, with chief complaint primer amenorrhea. The patient admit as a girl but not yet got her menstruation. Patient was referred by Endocrinology Fertility and Reproductive Consultant of OBGYN, that has done Cromosomal and Hormonal analysis. We perform a laparascopy Exploratif and we get no uterus, fallopian tubal and ovarium that are exist. But, we found testis in inguinal canal. Decision regarding gender assignment are still confronted between patient?s Family and medical staff. The prognosis is depends on the ambiguity of genital, Physical, and Physicosocial adjustment for sex assignment.